РЕКОНСТРУКЦИЯ СУЩЕСТВУЕЩЕГО ЖИЛОГО ДОМА RECONSTRUCTION OF AN EXISTING RESIDENTIAL BUILDING (International Conference on Medical Science, Medicine and Public Health, 2025)
The reconstruction of existing residential buildings is a process that addresses the need to improve living conditions, safety, and functionality of buildings while maintaining their structural integrity and, when possible, architectural value. This article explores the significance and complexity of reconstructing residential buildings, focusing on factors such as the analysis of the building's condition, modern technological solutions, energy efficiency, and environmental impact. The study emphasizes the necessity of balancing historical preservation with modern needs, and how new materials and methods can contribute to a sustainable and safe living environment.